2006
DOI: 10.1111/j.1572-0241.2006.00731.x
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Psychiatric/Medical Care in a Chronic Hepatitis C Clinic: Effect on Antiviral Treatment Evaluation and Outcomes

Abstract: An integrated MH and medical approach was associated with rates of antiviral therapy recommendation and initiation similar to patients without risks for psychiatric or substance use problems. MH care was associated with improved adherence to antiviral therapy. Integrated care offers promise as an approach for addressing psychiatric comorbidity in this traditionally difficult to treat population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(89 citation statements)
references
References 26 publications
3
83
0
1
Order By: Relevance
“…This is supported by previous study, which reported significantly greater adherence to antiviral therapy in a clinic based on an integrated mental health and medical approach (Knott et al, 2006). On the other hand, in the two hospitals with liaison psychiatry services, nurses said they had a tendency to over-rely on liaison psychiatrists, which may have exceeded the optimal level of referrals.…”
Section: Discussionsupporting
confidence: 72%
“…This is supported by previous study, which reported significantly greater adherence to antiviral therapy in a clinic based on an integrated mental health and medical approach (Knott et al, 2006). On the other hand, in the two hospitals with liaison psychiatry services, nurses said they had a tendency to over-rely on liaison psychiatrists, which may have exceeded the optimal level of referrals.…”
Section: Discussionsupporting
confidence: 72%
“…Decisions to start and adjust antiviral therapy were considered collaboratively with the clinic hepatologists. Patients with psychiatric and/or substance use co-morbidities were comanaged in consultation with the clinic psychiatrist, using model of co-managed care [12]. Colocalization of clinic personnel facilitated communication and patient "hand-offs", with same-day psychiatry appointments available as needed for patients undergoing treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Volunteers among primary care providers were recruited to participate. The clinic was organized along an integrated care model as previously described [12]. A co-located psychiatrist and pharmacist were integrated into the clinic, and bi-monthly noon meetings were held to discuss treatment issues.…”
Section: Methodsmentioning
confidence: 99%
“…Emotional support during the illness, before and after transplantation, both individually or in groups, can improve the emotional well being, HRQOL, survival, facilitate the adaptation and adherence of transplant candidates and transplant patients (Knott et al 2006;Quelhas & Steel, 2007). The goals of psychological intervention are to improve the QOL in patients with liver disease, facilitating their adaptation to the disease, accepting adaptive coping strategies and ultimately improving the patient's sense of self-control (Goetzmann et al, found in a sample of 69 patients, that almost half (47%) expressed the need for emotional support during the assessment for the procedure of liver transplantation (Goetzmann, 2007).…”
Section: Psychosocial Intervention In Patients With Advanced Liver DImentioning
confidence: 99%